2020
DOI: 10.1016/s2666-7568(20)30018-0
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy and survival in women aged 70 years and older with triple-negative breast cancer: a Swedish population-based propensity score-matched analysis

Abstract: Background Triple-negative breast cancer (TNBC) is an aggressive form of breast cancer associated with poor survival, in which adjuvant systemic treatments are limited to chemotherapy. Due to competing mortality risks and comorbidities, older patients with TNBC are often undertreated with adjuvant chemotherapy, and clinical trials on this problem are scarce, despite a growing patient population. This study aimed to assess outcomes for patients aged 70 years and older with TNBC with or without chemotherapy in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…In particular, a study by Slavica used the large cancer database of Sweden for their analysis and found that the 5-year OS of patients with adjuvant chemotherapy was 12% higher than that of patients who did not participate in chemotherapy through the propensity matching score method. Using the US National Cancer Database, another study by Jennifer also found that the 5-year OS of patients with adjuvant chemotherapy were 15% higher than that of patients who did not participate in chemotherapy ( 28 , 29 ). Recently, the object of several controversial reports focused on the value of adjuvant radiotherapy for TNBC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a study by Slavica used the large cancer database of Sweden for their analysis and found that the 5-year OS of patients with adjuvant chemotherapy was 12% higher than that of patients who did not participate in chemotherapy through the propensity matching score method. Using the US National Cancer Database, another study by Jennifer also found that the 5-year OS of patients with adjuvant chemotherapy were 15% higher than that of patients who did not participate in chemotherapy ( 28 , 29 ). Recently, the object of several controversial reports focused on the value of adjuvant radiotherapy for TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…The Kaplan-Meier curve in the low-risk group showed that the risk stratification system could accurately distinguish the OS of the total cohort, training cohort, and validation cohort. In all cohorts, the median OS was 56 (95% CI 52-63), while it was and 24 (95% CI [22][23][24][25][26][27][28] in the moderate-risk and high-risk groups, respectively, and no median survival was observed in the low-risk group.…”
Section: Risk Stratification Analysismentioning
confidence: 92%
“…Although nearly 80% of patients in our cohort had comorbidities, few had diseases that severely impacted their functional status, as only 4 patients scored CCI ≥3, which may partly explain the lack of correlation between comorbidities and treatment decisions or survival outcomes. The sample size of our study was smaller than that of other population-based studies ( 14 , 15 ), which may have limited our ability to analyze survival in relation to CCI values. The findings indicate that individualized assessment using developed tools such as the CCI are beneficial for estimating life expectancy and functional status among older patients with multiple comorbidities.…”
Section: Discussionmentioning
confidence: 87%
“…In the current study, comorbidity and the Charlson Comorbidity Index (CCI) failed to affect chemotherapy decisions and survival outcomes. A previous study revealed that chemotherapy is rarely recommended for older breast cancer patients with a CCI value ≥3 ( 3 ), and that patients with a higher CCI value had significantly worse OS outcomes ( 14 , 15 ). Based on the comorbid conditions listed in the CCI, we considered numerous highly prevalent comorbidities, such as hypertension ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation